ARTICAINE IN PEDIATRIC DENTISTRY – A REVIEW - Dr. Antra Saket; Dr. Sonal Gupta; Dr. Rohan Shrivastava; Dr. Priyambana Pandey; Dr. Sheenam Ayub (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Lidocaine is a tried-and-true local analgesia agent that has been used in dentistry for many years. Articaine is a newer generation of local anesthetic that has been gaining popularity in recent years. It is an amide type of analgesic, but it has unique structure i.e have a thiopene ring and thus is different from other amide analgesics. Articaine has faster onset of action, longer duration of anesthesia, and lower risk of side effects. Hence, it is a safe and effective local anesthetic in children that can be used to achieve successful pain control. This article examines the most recent research on the use of articaine in dentistry, paying particular attention to safety and efficacy concerns.